Psoriasis and daily low‐emission phototherapy: effects on disease and vitamin D level. Issue 2 (3rd December 2014) - Franken, Sylvie Mireille; Witte, Birgit; Pavel, Stan; Rustemeyer, Thomas
Abstract Background/Purpose Hospital‐based phototherapy is a widely accepted treatment modality in psoriasis patients. It, however, requires several hospital visits weekly, interfering with (school)work. Home ultraviolet (UV) treatment has been proven effective before but is only available in certain countries, and safety aspects play a part in reluctancy to prescribe this treatment. Patients, however, are usually keen on the use of phototherapy as it is effective and gives them the possibility of reducing the amount of topical treatment needed. In this study, we assess the effectivity of a low‐emission UV device used daily. Methods Sixty‐two patients were treated for 6 months either with daily low‐emission UV treatment and mometasone ointment 0.1% or with mometasone ointment 0.1% alone. Psoriasis severity scores, quality of life, vitamin D level, and blood pressure were monitored every 2 months during the study. Results Patients treated with daily low‐emission UV treatment showed a significant improvement in psoriasis severity, quality of life, amount of steroid ointment used, and vitamin D levels. Conclusion Daily low‐emission UV therapy is an effective treatment for psoriasis patients, diminishing the amount of steroid ointment needed and improving disease activity, quality of life, and vitamin D scores. Further investigation, however, is necessary.